PENGEMBANGAN METODE IQRA TERPADU DALAM MENINGKATKAN MINAT BELAJAR AL-QUR’AN PADA SISWA KELAS TINGGI DI SDN RANCAILAT CIKANDE SERANG - N. Atiyah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
This research aims (1). To find out how to analyze the integrated iqra method in learning to read and write the Qur'an at SDN Rancailat, Bakung Village, Kec. Cikande Kab. Serang, (2). To find out students' interest in learning to read and write the Qur'an at SDN Rancailat, Bakung Village, Kec. Cikande Kab. Serang, (3). To find out the Implement of the Integrated Iqra Method can increase interest in learning to read and write the Qur'an in students of SD Negeri Rancailat, Bakung Village, Kec. Cikande Kab. Attack, (4). To find out the Integrated Iqra Method can increase interest in learning the Qur'an at SD Negeri Rancailat, Bakung Village, Kec. Cikande Kab. Attack. The research method used is descriptive qualitative method. Sources of data obtained from direct observation and in-depth interviews, documentation, and questionnaires. Subjects determined in this study were principals, PAI teachers, BTQ teachers and 40 students. The data analysis used were: data reduction, data presentation, and conclusion drawing. The results of this study indicate that the integrated iqra method in learning to read and write the Qur'an at SDN Rancailat in this good category is obtained from the results of the analysis reaching the percentage: 75%. The development of the Integrated Iqra Method can increase interest in learning to read and write the Qur'an in students of SD Negeri Rancailat, Bakung Village, Kec. Cikande Kab. Serang is in the very good category, reaching a lift of 81% seen from the results of respondents' answers always and the results of interviews with writers and teachers that it is true that in learning to read and write the Qur'an at SDN Rancailat, my students are very enthusiastic in learning to read and write the Qur'an. an because I use the integrated iqra method. implementation of the Integrated Iqra Method of learning to read and write the Qur'an at SD Negeri Rancailat, Bakung Village, Kec. Cikande Kab. Serang as a whole based on the results of student answers, teachers in teaching reading and writing the Qur'an at SDN Rancailat can be categorized as good. This is evidenced by the results of their ability to read and write the Qur'an using the Iqra method, they are very enthusiastic in following each stage, both Iqra volumes 1 to 6 plus writing Arabic letters or the Qur'an and memorizing Juz 'Amma/Juz 30.